The Influence of Money Politics on Public Participation in Electing Regional Head Candidates in 2024 in Suka Maju Village, Pahae Jae District, North Tapanuli Regency, Siyasah Dusturiyah Perspective - Br Ginting, Sofa Edininta; Fatimah, Fatimah (LEGAL BRIEF, 2025)
This study aims to analyze the influence of money politics on public participation in the 2024 regional head elections in Suka Maju Village, North Tapanuli Regency, from the perspective of Siyasah Dusturiyah (state politics in Islam). Money politics, which involves the provision of material or other rewards to influence political choices, is considered a practice that undermines democratic values ??and violates the principle of justice in Islam. This study used a qualitative approach with field studies, in-depth interviews, and documentation. The results show that the practice of money politics is still widespread and has a significant influence on the voting decisions of some residents, especially those in low economic conditions. However, there are also community groups who reject money politics based on ethical awareness and religious values. From the perspective of Siyasah Dusturiyah, money politics contradicts the principles of justice, trustworthiness, and deliberation, which are the basis for electing leaders with integrity. Therefore, political education and strengthening of Islamic values ??are needed so that public political participation is not based on material rewards, but rather on moral considerations and the quality of prospective leaders